1999
DOI: 10.1091/mbc.10.9.2861
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of β1-Integrin Function by Epidermal Growth Factor and Heregulin-β Has Distinct Requirements for erbB2 but a Similar Dependence on Phosphoinositide 3-OH Kinase

Abstract: Integrins and growth factor receptors are important participants in cellular adhesion and migration. The EGF receptor (EGFR) family of tyrosine kinases and the beta1-integrin adhesion receptors are of particular interest, given the implication for their involvement in the initiation and progression of tumorigenesis. We used adhesion and chemotaxis assays to further elucidate the relationship between these two families of transmembrane signaling molecules. Specifically, we examined integrin-mediated adhesive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 70 publications
6
55
0
Order By: Relevance
“…228 Contributions of ERBB3 and/or the ERBB2/ ERBB3 complex to these phenotypic effects of NRG has been confirmed by use of anti-ERBB2 or anti-ERBB3 antibodies 211,212,229 or of a dominant-negative ERBB3 construct. 230 The downstream participation of PI3K or pAKT was confirmed in some of these studies by use of pharmacological or dominant-negative inhibitors of PI3K 209 or by constitutively active constructs of the p110 catalytic subunit of PI3K and by pharmacological inhibition of AKT. 213 Additional signal transducing molecules, potentially important for the malignant phenotype, such as JNK, MAPK and p38 MAPK, have been implicated downstream of NRG in mammary cancer cells, along with altered transcription of cancer-related genes such as matrix metalloproteinases, urokinase plasminogen activator, vascular endothelial growth factor, angiogenic factor Cyr61, autocrine motility factor, HIF1α, activating transcription factor 4, GADD153, estrogen and progesterone receptors and BRCA1 (reviewed in 82 ).…”
Section: Erbb3 In Normal and Neoplastic Tissues Cell Transformation Bmentioning
confidence: 90%
See 2 more Smart Citations
“…228 Contributions of ERBB3 and/or the ERBB2/ ERBB3 complex to these phenotypic effects of NRG has been confirmed by use of anti-ERBB2 or anti-ERBB3 antibodies 211,212,229 or of a dominant-negative ERBB3 construct. 230 The downstream participation of PI3K or pAKT was confirmed in some of these studies by use of pharmacological or dominant-negative inhibitors of PI3K 209 or by constitutively active constructs of the p110 catalytic subunit of PI3K and by pharmacological inhibition of AKT. 213 Additional signal transducing molecules, potentially important for the malignant phenotype, such as JNK, MAPK and p38 MAPK, have been implicated downstream of NRG in mammary cancer cells, along with altered transcription of cancer-related genes such as matrix metalloproteinases, urokinase plasminogen activator, vascular endothelial growth factor, angiogenic factor Cyr61, autocrine motility factor, HIF1α, activating transcription factor 4, GADD153, estrogen and progesterone receptors and BRCA1 (reviewed in 82 ).…”
Section: Erbb3 In Normal and Neoplastic Tissues Cell Transformation Bmentioning
confidence: 90%
“…205 The conclusion that an ERBB2/ERBB3 complex constitutes a high affinity ligand for NRG 110 has been amply confirmed in mammary carcinoma cells, along with mutual phosphorylating transactivation by ERBB2 and ERBB3. 175,176,185,[205][206][207][208][209][210][211][212][213][214][215][216] ERBB3 can also be transactivated by the EGFR in mammary cancer cells. 105,217 Different breast cancer cell lines show considerable variability with regard to relative expression, colocalization, responsiveness and activity of ERBB3 and the other ERBB receptors.…”
Section: Erbb3 In Normal and Neoplastic Tissues Cell Transformation Bmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, genetic and biochemical analyses have revealed that the a6b1 integrin receptor can associate with activated members of the EGFR family (Weaver et al 1997). Stimulation of b1 integrin function can thereby result in the enhanced phosphorylation of EGFR family members (Adelsman et al 1999;Mariotti et al 2001;Moro et al 1998). Moreover, activation of TGF-b signaling can induce coclustering of b1-integrin and ErbB2, and thereby promote metastatic invasion (Wang et al 2009a).…”
Section: Oncogene-integrin Cross Talk In Mammary Tumor Progressionmentioning
confidence: 99%
“…Adhesion to ECM maintains or modulates the response to soluble growth factors (Miyamoto et al, 1996;Lee and Streuli, 1999;Renshaw et al, 1999;Yarwood and Woodgett, 2001) or induces phosphorylation of growth factor receptors (Moro et al, 1998;Yu et al, 2000). On the other hand, growth factor stimulation changes the expression of integrins and the cellular adhesive activity (Lichtner et al, 1995;Wang et al,1998;Adelsman et al,1999). Further, physical association of growth factor receptors with integrins was indicated by immunoprecipitation experiments (Schneller et al, 1997;Soldi et al, 1999;Trusolino et al, 2001).…”
Section: Introductionmentioning
confidence: 99%